A 3D topological auto-routing algorithm for mechatronic products design. Issue 10 (3rd October 2017) - Zhan, Huixian; Zhuo, Yong; Wu, Xuan; Chen, Junfa; Pan, Junhao
Abstract : New technologies, like 3D-MID (Three Dimensional - Mechatronic Integrated Devices), Flex Circuits and jet-printing technology for mechatronic products, raise requirement for integrated design, in which 3D layout is crucial. However, research on 3D routing algorithm is far from enough. Current 3D auto-routing algorithms are mainly based on 2D geometry routing algorithms. Geometric routing algorithms are usually used on regular geometry, bringing limitations in routing directions. Besides, existing 3D routing algorithms did not break through geometry structures' constraints of 3D routing bases. A 3D topological auto-routing algorithm based on rubber-band routing was proposed in this paper. First, a new dynamic 3D search graph based on a triangular mesh was established. The 3D search graph concludes adjacent relations among different surfaces, getting rid of 3D surface limitation, even for curved surface. The renewal of the search graph assures that routes won't cross through each other. In addition, the data structure combining hash table and adjacency list was used to store the 3D search graph, which reduces the storage space and promotes the algorithm efficiency. Afterwards, the generation of rubber bands was realised on modified A* algorithm and funnel algorithm. And then, append appropriate spokes to obtain extended rubber bands, which are treated as shortest paths theoretically.